Phenotypes on demand via switchable target protein degradation in multicellular organisms - Frederik Faden (Nature Portfolio, 2016)
Switching target protein accumulation and activity by portable conditional degrons is potentially useful for both basic research and bioengineering. Here the authors present a versatile system to tune protein levels in live animals and plants using a temperature-sensitive N-end rule degradation signal.